2014
DOI: 10.1073/pnas.1310777111
|View full text |Cite
|
Sign up to set email alerts
|

A heterozygous mutation of GALNTL5 affects male infertility with impairment of sperm motility

Abstract: For normal fertilization in mammals, it is important that functionally mature sperm are motile and have a fully formed acrosome. The glycosyltransferase-like gene, human polypeptide N-acetylgalactosaminyltransferase-like protein 5 (GALNTL5), belongs to the polypeptide N-acetylgalactosamine-transferase (pp-GalNAc-T) gene family because of its conserved glycosyltransferase domains, but it uniquely truncates the C-terminal domain and is expressed exclusively in human testis. However, glycosyltransferase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…Notably, GALNTL5 also temporarily localizes in the acroplaxome and manchette, which is a transient microtubular/actin structure, during spermatid elongation and finally accumulates in the neck region around the head-tail coupling apparatus of mature spermatozoa. These findings lend strong evidence for GALNTL5 being involved in spermiogenesis (Takasaki et al, 2014).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Notably, GALNTL5 also temporarily localizes in the acroplaxome and manchette, which is a transient microtubular/actin structure, during spermatid elongation and finally accumulates in the neck region around the head-tail coupling apparatus of mature spermatozoa. These findings lend strong evidence for GALNTL5 being involved in spermiogenesis (Takasaki et al, 2014).…”
Section: Introductionsupporting
confidence: 58%
“…In the spermatozoa of heterozygous mutant mice, some researchers observed impairment of protein loadings into acrosomes and aberrant localization of the ubiquitin-proteasome system. Moreover, colocalization of GALNTL5 signals with UBC3B, an E2 ubiquitin conjugating enzyme similar to UBC3/CDC34, and ubiquitin signals was observed in the ubiquitin-proteasome system in the neck region of spermatozoa from wild-type mice (Takasaki et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In order to investigate the biological role of human GALNTL5 (7q36.1) in the testis, the localization of the mouse orthologous protein, GALNTL5, was observed in spermatogenesis and Galntl5 ‐deficient mice were established 87. The heterozygous mutant male mice were infertile because of their immotile spermatozoa, a feature that corresponded to human azoospermia 87.…”
Section: Culprit Genes That Have Been Identified In Autosomesmentioning
confidence: 99%
“…It also was reported that the heterozygous mutation of Galntl5 in mice impaired the amounts of glycolytic enzymes that are required for motility, protein loading into the acrosomes, and localization of the ubiquitin–proteasome system in the neck region in the spermatozoa, which consists of common cytoplasmic constituents that are shared among the haploid spermatids through intracellular bridges 88, 89. Screening for male patients with infertility that was caused by a mutation of the GALNTL5 gene was conducted and one patient was identified among 200 whose asthenozoospermia was attributable to a heterozygous single nucleotide deletion of maternal inheritance in the exon of GALNTL5 87. This strongly suggests that the genetic mutation of human GALNTL5 results in male infertility, with a reduction of sperm motility, and that GALNTL5 is a protein that is essential for mammalian sperm formation.…”
Section: Culprit Genes That Have Been Identified In Autosomesmentioning
confidence: 99%